Phragmites australis: Anaerobic constructed wetland Fe (II) concentration Total solids and pH in AMD (LACCEI, 2024)
In the present research work, the concentrations of Fe (II), total solids, in addition to the pH variations, were determined as a function of the retention time of real water samples from an acid drainage of a coal mining unit. abandoned, using a Batch-type anaerobic artificial wetland. The water samples were taken from the Perejil river, which is located at 3981.5 masl The acid drainage (AMD) used remained a total of 132 hours in the constructed artificial wetland the samples were taken every 12 hours Fe (II) was determined by atomic absorption the determination of total solids was carried out by gravimetric method while the pH values were made by instrumental measurement. The plant species used in the construction of the wetland was the so-called Phragmites australis (reed) From the results obtained, we can mention that the increase in the DAM retention time in the artificial wetland used decreases the initial concentrations of Fe(II) and total solids in addition to increasing the pH values of the DAM the Fe(II) removal percentages obtained after 48 hours of wetland use reached a maximum value of 98.488% in the case of total solids, the maximum removal percentage was 76.134% in 132 hours of wetland use while the pH of the DAM fluctuated between 3.2 (beginning) up to a value of 7.4 at 48 hours In addition, it was evidenced that in the case of Fe(II) at a retention time of 12 hours, the removal percentage was already 95.685% equivalent to the same number of hours, the pH of the DAM was already 6.4 Therefore, the use of the wetland should be evaluated at times greater than 12 hours.